Psoriasis Rupioid pada Pasien Pengidap Human Immunodeficiency Virus: Laporan Kasus - Mellyanawati, .; Palimbong, Florencia; Kapantouw, Grace M.; Niode, Nurdjannah J. (UNIVERSITAS SAM RATULANGI, 2019)
Abstract: Psoriasis can occur in patients with human immunodeficiency virus (HIV), but the clinical features are very unusual and difficult to establish as a diagnosis. One of the rare types of psoriasis is rupioid psoriasis that often occurs in immunocompromised patients marked with the presence of thick crusts in cone and limpet-like shapes. Definite diagnosis is usually made by performing a histo-pathological skin biopsy, and other supporting investigations to rule out differential diagnoses. The main therapy for psoriasis in HIV patients is phototherapy and antiretroviral drugs, besides that topical therapy and immunosuppressants should be considered according to the patientsâ€™ condition. We reported a male, aged 38 years, with complaints of thick crusts on the skin almost the entire body since 2 months ago, accompanied by a slight itchy feeling. On clinical examination, erythematous plaques were found accompanied by thick crusting with cone and limpet-like shapes. Anti-HIV was reactive, CD4 <200 cells/Î¼L, and histopathology examination of skin biopsy led to the diagnosis of psoriasis. Based on these clinical findings and investigations, diagnosis of rupioid psoriasis was established. The patient showed significant improvement after being treated with symptomatic systemic drugs and topical steroids for 3 weeks.Keywords: rupioid psoriasis, human immunodeficiensy virus, topical steroidÂ Abstrak: Psoriasis dapat terjadi pada pasien dengan human immunodeficiency virus (HIV), namun gambaran klinisnya sangat tidak khas dan sulit untuk didiagnosis. Salah satu tipe yang jarang dari psoriasis tersebut ialah psoriasis rupioid yang sering muncul pada pasien dengan imunokompromais, dengan gambaran klinis adanya krusta tebal berbentuk kerucut dan limpet. Diagnosis pasti biasanya ditegakkan dengan melakukan biopsi kulit histopatologik, dan pemeriksaan penunjang lainnya untuk menyingkirkan diagnosis banding. Terapi utama untuk psoriasis pada pengidap HIV yaitu fototerapi dan ARV. Pemberian terapi topikal dan imunosupresan perlu dipertimbangkan sesuai dengan kondisi pasien. Kami melaporkan kasus seorang laki-laki, berusia 38 tahun, dengan keluhan timbul keropeng tebal pada kulit hampir seluruh tubuh, sejak 2 bulan lalu disertai rasa sedikit gatal. Pada pemeriksaan klinis didapatkan adanya plak eritematosa yang disertai krusta tebal dengan bentuk kerucut dan limpet. Pemeriksaan anti HIV reaktif, CD4 <200 sel/Î¼L, dan pemeriksaan biopsi kulit histopatologik mengarah ke diagnosis psoriasis. Berdasarkan temuan klinis dan pemeriksaan penunjang tersebut, diagnosis psoriasis rupioid ditegakkan. Pasien menunjukkan perbaikan nyata setelah diterapi dengan obat sistemik simptomatik dan topikal steroid selama 3 minggu.Kata kunci: psoriasis rupioid, HIV, topikal steroid